Keterlibatan Ayah Dalam Pemberian Stimulasi Tumbuh Kembang Pada Anak Prasekolah - Dita Sulistyowati (Poltekkes Kemenkes Jakarta III, 2019)
Stimulation of growth and development in children including pre-school age children is very important to do by parents and families. This is done to stimulate the ability and growth and development of children to grow and develop optimally in accordance with the stages of development. Many factors affect parents in providing growth and development stimulus in pre-school age children. One of them is the involvement of fathers in childcare. The purpose of this study was to obtain a picture of the factors that influence parents in providing stimulation of preschool children growth and development. The research design used was descriptive research with cross-sectional study. Data analysis using component analysis with univariate and bivariate analysis. The results showed that the father's involvement variable influences the provision of growth and growth stimulation in pre-school children (p value = 0.001), and OR = 10.978 which means that respondents who have father involvement in good stimulation have an opportunity for mothers 10.9 times better in doing growth and growth stimulation on their children compared to respondents who had less father involvement in stimulation. The involvement or role of fathers in the stimulation of growth and development becomes an important aspect for children's development.